Print and production finishes for packaging - Denison, Edward ([S.l.] : Rockport Publishers, 2008)
With informative text and specially commissioned full-color photos, Print and Production Finishes for Packaging shows, at a glance, the different effects that can be created, and the key print and production techniques used to achieve them. Work across all budgets and production/print runs is featured, revealing the skills and techniques that grab the target audience$1 (Bs attention and sell. For print and production finishing ideas on everything from boxes, cartons, bottles, tubes, cans, packs, tubs, jars, multi-packs, clamshells, blister packs, CDs or DVDs, gift packs, and a variety of other more unusual or innovative formats, Print and Production Finishes for Packaging is an indispensable ideas sourcebook and practical guide to finishes, surface graphics, detailing, and materials that help make packaging stand out from the crowd$1 (Bincluding foil blocking, pigment blocking, thermography, varnishing, laminating, embossing, debossing, die-cutting and laser-cutting; specialist inks, including metallics and fluorescents; different papers stocks and other materials; lenticular printing, and so on. By analyzing the best in the business, this book gives readers a thorough understanding of materials, and of the print and production finishes that can be applied to any job.s
Keywords: Packaging--Design